ANALISIS PERAN SEKTOR PERTANIAN DALAM MENDUKUNG PEMULIHAN EKONOMI MASA PANDEMI COVID 19 DI KOTA BATU - Alvina Zahra Wicaksana (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study analyzes the role of the agricultural sector in supporting economic recovery during the pandemic. As a result of the PSBB policy at the beginning of Covid 19 entering Indonesia, many economic sectors have stagnate, but the agricultural sector in Batu City is still in a positive number and is included in the leading sector. Leading sectors can sustain and help other economic sectors collapse due to the pandemic. The research method used is descriptive qualitative using secondary data from articles, journals, literature, and mass media as well as BPS data. Data collection techniques using research articles and literature review. The leading sector analysis uses Klassen typology analysis whose output is a sector classification in 4 quadrants. The results of the Klassen typology analysis reveal that the agricultural sector is a developed sector and is growing rapidly . The results of the study reveal several strategies carried out by the Department of Agriculture and Food Security in Batu City in supporting the economic recovery of the agricultural sector, namely Food Security in Batu City, creating an Organic Yard Intensification (IPO) and Sustainable Food Garden (P2L) program as well as preparing five strategies to support recovery in the agricultural sector. .